First direct evidence of Chalcolithic footwear from the Near Eastern Highlands - Pinhasi, R; Gasparian, B; Areshian, G; Zardaryan, D; Smith, A; Bar-Oz, G; Higham, T (Public Library of Science, 2010)
In 2008, a well preserved and complete shoe was recovered at the base of a Chalcolithic pit in the cave of Areni-1, Armenia. Here, we discuss the chronology of this find, its archaeological context and its relevance to the study of the evolution of footwear. Two leather samples and one grass sample from the shoe were dated at the Oxford Radiocarbon Accelerator Unit (ORAU). A third leather sample was dated at the University of California-Irvine Accelerator Mass Spectrometry Facility (UCIAMS). The R_Combine function for the three leather samples provides a date range of 3627–3377 Cal BC (95.4% confidence interval) and the calibrated range for the straw is contemporaneous (3627–3377 Cal BC). The shoe was stuffed with loose, unfastened grass (Poaceae) without clear orientation which was more than likely used to maintain the shape of the shoe and/or prepare it for storage. The shoe is 24.5 cm long (European size 37), 7.6 to 10 cm wide, and was made from a single piece of leather that wrapped around the foot. It was worn and shaped to the wearer's right foot, particularly around the heel and hallux where the highest pressure is exerted in normal gait. The Chalcolithic shoe provides solid evidence for the use of footwear among Old World populations at least since the Chalcolithic. Other 4th millennium discoveries of shoes (Italian and Swiss Alps), and sandals (Southern Israel) indicate that more than one type of footwear existed during the 4th millennium BC, and that we should expect to discover more regional variations in the manufacturing and style of shoes where preservation conditions permit.